1980
DOI: 10.1073/pnas.77.8.4489
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure of pro-somatostatin: a putative somatostatin precursor from pig hypothalamus.

Abstract: An octacosapeptide that we named pro-somatostatin has been isolated from acid extracts of porcine hypothalami and found to have the amino acid sequence Ser-AlaAsn-Ser-Asn-Pro-:Ala-Met-Ala-Pro-Arg-Glu-Arg>Lys-Ala-GlyCys-Lys-Asn-Phe-Phe-Trp-Lys-Thr-Phe-Thr-Ser-C's. This octacosapeptide possesses high somatotropin (growth hormone) and prolactin release-inhibiting activity in vitro. It also crossreacts strongly with antisera generated against the somatostatin tetradecapeptide. This octacosapeptide is most likely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(64 citation statements)
references
References 38 publications
4
59
1
Order By: Relevance
“…We have previously characterized SLI in rat hypothalamus and identified three forms of immunoreactivity: one with a molecular weight of 15,000, comprising -5% of total SLI (15,000-mol-wt SLI); a second form of Mr = 3,000 (3,000-mol-wt SLI) accounting for -25% of total SLI; and a third, dominant form of Mr = 1,600 (-70% of total SLI), which corresponds to SRIF (6). Recent amino acid analyses have established the identity of 1,600-mol-wt SLI with SRIF (16) and of 3,000-mol-wt SLI with that of somatostatin-28 (S-28) (17), a biologically active 14 amino acid N-terminally extended form of SRIF isolated from mammalian hypothalamus and intestine (18)(19)(20). Our earlier investigations on the processing of 15,000-mol-wt SLI and S-28 by hypothalamic enzymes support a possible role for both peptides as precursors for S-14 (21,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously characterized SLI in rat hypothalamus and identified three forms of immunoreactivity: one with a molecular weight of 15,000, comprising -5% of total SLI (15,000-mol-wt SLI); a second form of Mr = 3,000 (3,000-mol-wt SLI) accounting for -25% of total SLI; and a third, dominant form of Mr = 1,600 (-70% of total SLI), which corresponds to SRIF (6). Recent amino acid analyses have established the identity of 1,600-mol-wt SLI with SRIF (16) and of 3,000-mol-wt SLI with that of somatostatin-28 (S-28) (17), a biologically active 14 amino acid N-terminally extended form of SRIF isolated from mammalian hypothalamus and intestine (18)(19)(20). Our earlier investigations on the processing of 15,000-mol-wt SLI and S-28 by hypothalamic enzymes support a possible role for both peptides as precursors for S-14 (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the experiments described here were designed both to demonstrate biosynthesis in nerve cells and to provide insight into the biosynthetic relationship between the three molecular forms of SLI. [17][18][19][20][21]. The cells were suspended in 20 ml of Dulbecco's modified Eagle's medium (DME) and plated in 35-mm-Diam plastic Petri dishes (Falcon Labware, Div.…”
Section: Introductionmentioning
confidence: 99%
“…3 It is also released by isolated pancreatic islets in perifusion experiments. 4 Its structure is that of the tetradecapeptide somatostatin (SRIF) with a 14-amino-acid amino terminal extension.…”
mentioning
confidence: 99%
“…It has been suggested that S-28 is a precursor of SRIF. 3 However, since S-28 is more active than SRIF in some biologic systems, 5 it is also possible that S-28 may represent a naturally occurring form of somatostatin discrete from SRIF. S- 28 has not yet been identified in the circulation.…”
mentioning
confidence: 99%
“…In the central nervous system, it is distributed throughout various brain areas [4] together with another form: somatostatin- [5]. Somatostatin-28, first discovered in both porcine intestine [6] and hypothalamus [7] and in ovine hypothalamus [8,9], corresponds to an NHz-terminally extended somatostatin-14 containing 28 amino acids.…”
Section: Introductionmentioning
confidence: 99%